Procedures for Implementing Supervision and Evaluation - Nuril Fitria Hidayati; Wati Wati; Maghfiroh Maghfiroh (Comprehensive: Jurnal Ilmu Pendidikan dan Keguruan, 2026)
The supervision and evaluation implementation procedure consists of several main, interconnected stages to ensure the learning process runs effectively and meets standards. The first stage is planning, where the supervisor sets objectives, develops a schedule, and selects a supervisory approach and instruments. The second stage is the implementation of supervision, which includes pre-observation to establish communication and focus observations, direct observation of the learning process without judgment, and analysis of the observation results to identify positive aspects and areas for improvement. The third stage is evaluation and follow-up, where the analysis results are presented to the teacher in a post-observation meeting as feedback, which includes appreciation, input, and motivation to improve competency. Finally, a supervision report is prepared as documentation and a reference for continuous improvement. The success of supervision depends heavily on the active involvement of teachers and the support of the principal and other relevant stakeholders. Educational supervision is a teacher development effort to improve the quality of the learning process in Madrasahs. The objectives of this study were to determine: the educational supervision program; the techniques for implementing educational supervision; the process of implementing educational supervision; and the follow-up to the implementation of educational supervision. The subjects of this study consisted of supervisors, Madrasah principals, and the teaching staff. The method used in this study was a literature review to analyze the procedures for implementing supervision and evaluation. The results of this study indicate that supervision and evaluation procedures need to be carried out comprehensively, objectively, and sustainably, involving all relevant parties, including all supervisors, teachers, principals, and students. This ensures that the evaluation is comprehensive, fair, and able to provide constructive feedback for improving the quality of learning.